Gram-positive, motile, cluster-forming cocci as a cause of urinary infection - Virtanen, S. (1974)
One hundred and thirteen strains of motile, Gram-positive, catalase-positive, cluster-forming cocci were isolated from patients with urinary infection attending a private surgery. They constituted 1% of the total 11 302 positive cultures. The biochemical characteristics and the drug sensitivities of the strains are described. The significance of motility for organisms which cause urinary infections is pointed out. At the present time the organisms isolated are orphans in the controversial classification of staphylococci and micrococci.